The Kurdish question in Syria and Turkey in the middle of the XX century – beginning of XXI century. (Journal of Oriental Studies, 2016)
This article examines the Kurdish quiestion in Sirya and Iraq amd the role of kurds in social and political life of these countries.
Keywords: Kurdish problem; ethnicity; party; region